Simulated warmer winter reduces the effectiveness of insecticides in oilseed rape, but has little effect on pollinator activity - Bishop, Gabriella A.; Rundlöf, Maj ; 0000-0003-3014-1544; Tájmel, Dániel; Olsson, Pål Axel; Smith, Henrik G. ; 0000-0002-2289-889X; Klatt, Björn K. ; 0000-0001-8241-6445 (Agriculture, Ecosystems and Environment, 2026)
Climate change may affect the yield of mass-flowering crops by altering the interplay between pest pressure and service delivery by pollinators, but realistic predictions need to account for the frequent use of insecticides in conventional farming. We tested the interactive effects of insecticide use and warmer winter conditions on oilseed rape (Brassica napus) production, pest pressure, and the activity of Bombus terrestris, an important bumblebee pollinator. We evaluated the effects of three different insecticides at two different concentrations. We found that winter warming reduced the effectiveness of two insecticides against pollen beetles in comparison to the control (no insecticides), likely due to the dilution of insecticides on plants with increased plant size. Additionally, plots treated with reduced concentrations of insecticides generally had similar levels of pollen beetles as those with standard concentrations. There were no interactive effects of insecticide application and winter warming on pollinator activity or oilseed rape yield. However, yield quality was negatively affected by winter warming. Under current winter conditions, reduced insecticide applications may provide pest control comparable to standard applications and could therefore serve as an integrated pest management strategy. Under future winter conditions, such strategies will likely need to consider the effects of climate change on plant development, because the overall effectiveness of insecticide treatment against pests could decrease.
Keywords: Bees; Climate change; IPM; Pest control; Pesticides; Pollination